The Effect of the Use of Progestin Contraception Pills and Combinations on Adequate Production of Exclusive Breast Milk in Breastfeeding Women - Lili Farlikhatun; Nunung Sukaemi (STIKep PPNI Jawa Barat, 2023)
Aims: To determine the effect of the use of progestin and combined contraceptive pills on the adequacy of exclusive breast milk production in breastfeeding mothers Methods: This study employs quantitative research with a cross-sectional research design. This study included all breastfeeding mothers who came to the Lemahabang Public Health Center to use pill contraception, a total of 137 people. The sample in this study was 58 people using the purposive sampling technique. Bivariate analysis using chi-square test. Results: Most of the people using progestin pill contraceptives do not, namely 36 people (62.1%). Most of the used combination pills did not, namely 39 people (67.2%). The adequacy of exclusive breast milk production for breastfeeding mothers is mostly not enough, namely as many as 35 people (60.3%). Conclusion: It can be concluded that there is an effect of the use of progestin and combined contraceptive pills on the adequacy of exclusive breast milk production in breastfeeding mothers in the Work Area of ​​the Lemahabang Health Center, Karawang Regency 0.05. It is recommended that breastfeeding mothers seek information about the right contraception for themselves before choosing, especially breastfeeding mothers who want to choose contraception so that their milk production is not affected or reduced.